Max Planck School of Photonics: Developing Curriculum and Outreach Measures for a Network of Excellence - Geiss, Reinhard; Hengster, Julia; Grimm, Anna Katharina; Kaiser, Thomas; Leuchs, Gerd; Tünnermann, Andreas (Optics InfoBase Conference Papers, 2021)
The Max Planck School of Photonics is an interdisciplinary graduate school in Germany providing an integrated MSc and PhD program for international students. Aspects of curriculum development and outreach measures will be presented and discussed.
CRIS-Team Scopus Importer:2023-04-20